JavaScript testing with Jasmine - Hahn, Evan (O'Reilly Media, 2013)
Get a concise introduction to Jasmine, the popular behavior-driven testing framework for JavaScript. This practical guide shows you how to write unit tests with Jasmine that automatically check for bugs in your application. If you have JavaScript experience--with knowledge of some advanced features--you'll learn how to write specifications for individual components, and then use those specs to test the code you write. Throughout the book, author Evan Hahn focuses primarily on methods for testing browser-based JavaScript applications, but you'll also discover how to use Jasmine with CoffeeScript, Node.js, Ruby on Rails, and Ruby without Rails. You won't find a more in-depth source for Jasmine anywhere. Get an overview of both test-driven and behavior-driven development Write useful specs by determining what you need to test--and what you don't Test the behavior of new and existing code against the specs you create Apply Jasmine matchers and discover how to build your own Organize code suites into groups and subgroups as your code becomes more complex Use a Jasmine spy in place of a function or an object--and learn why it's valuable.